2006
DOI: 10.1144/gsl.sp.2006.267.01.03
|View full text |Cite
|
Sign up to set email alerts
|

The Avaatech XRF Core Scanner: technical description and applications to NE Atlantic sediments

Abstract: X-ray fluorescence (XRF) core scanning provides rapid high-resolution (down to 1 mm) records of chemical composition on split sediment cores. The measurements are non-destructive and require very limited sample preparation. The new Avaatech XRF Core Scanner, operational since 2002, covers the atomic mass range from Al to U. Instrument parameters, especially tube voltage, can be adjusted to provide optimum settings for selected elements or sets thereof. Owing to the nature of the surface of split sediment cores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
340
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 364 publications
(350 citation statements)
references
References 24 publications
2
340
0
8
Order By: Relevance
“…feldspars and clays) and biogenic carbonates (e.g. Richter et al, 2006, Foubert and Henriet, 2009, Rothwell and Croudace, 2015. Based on these observations, we interpret that Ca in our sediments is mainly of biogenic origin (CaCO 3 ).…”
Section: Geochemistrysupporting
confidence: 58%
See 1 more Smart Citation
“…feldspars and clays) and biogenic carbonates (e.g. Richter et al, 2006, Foubert and Henriet, 2009, Rothwell and Croudace, 2015. Based on these observations, we interpret that Ca in our sediments is mainly of biogenic origin (CaCO 3 ).…”
Section: Geochemistrysupporting
confidence: 58%
“…This non-destructive method yields element intensities on the surface of split sediment cores and provides statistically significant data for major and minor elements (Richter et al, 2006;O'Regan et al 2010, Wilhelms-Dick et al, 2012. Detailed bulk-chemical composition records acquired by XRF core scanning allows accurate determination of sedimentological changes as well as assessment of the contribution of the various components in the biogenic and lithogenic fraction of the marine sediments 230 (Croudace et al, 2006).…”
mentioning
confidence: 99%
“…The here reported data have been acquired by XRF Core Scanner I at MARUM using a KEVEX Psi Peltier Cooled Silicon Detector and a KEVEX X-ray Tube 52500008-02 with the target material molybdenum (Mo). The detection limit for iron for the XRF scanner used is 210 ppm (Richter et al 2006). Repeatability tests at the surface of split sediment core halves have shown that the error is smaller than 1% if the core surface is of high quality (Röhl and Abrams, 2000), which was the case for the scanned core sections of this study.…”
Section: Stable Isotope Measurements Ird and Fe Concentrationmentioning
confidence: 57%
“…1). The XRF core-scanning measurements of the ACEX cores were obtained directly at the split core surface of the archive half for the upper 20 m of the composite section using the XRF core scanner I at the University of Bremen (Rö hl and Abrams, 2000), which is an updated version of the CORTEX scanner (Richter et al, 2006). The XRF scanner measurements were carried out with a KEVEX Ó X-ray tube, a Mo detector, a generator setting of 20 kV and a sampling time of 30 s to obtain the element intensities from K through to Sr.…”
Section: Methodsmentioning
confidence: 99%